A case study: SMED contributor using Shapley value - S. S., Sulaiman; Muhamad Arifpin, Mansor (Malaysian Technical Universities Network (MTUN), 2017)
Single Minute Exchange Die (SMED) is one of lean tools to reduce setup time. Throughout the application of SMED, the effectiveness of this tool is unknown because there is no method to calculate its performance measurement. As long as time reduction takes place, the implementation of SMED achieves its target and goal. However, throughout the implementation of SMED most companies pay more attention on reducing time in their activity, but do not take into consideration the performance during the time reduction process. Therefore, the Shapley value method is applied to identify the performance of SMED during the time reduction process occur. In this method, a game theory concept is used to calculate the testing factors that need to be measured: time, machines, activities etc. where testing factors can represent as player and contributor. From the calculation, a fair coalition among testing factors can be identified and elimination of the unnecessary activities during the time reduction process is measured.